Analisis Kualitas Air, Limbah dan Udara pada Industri Perhotelan: Studi Kasus Hotel X di Yogyakarta - Saprian, Saprian; Siswoyo, Eko (Jurnal Sains dan Teknologi Lingkungan, 2024)
Environmental quality is one of the key factors in supporting the tourism industry, where good environmental conditions are expected to be an attraction for tourists to visit a city. Various environmental problems such as pollution of river water bodies, ground water and air must receive serious attention, for example through environmental quality monitoring activities by hotel industry players. The current research aims to evaluate environmental quality conditions in four-star hotels and provide recommendations for improvement. Data collection was carried out by surveys and direct monitoring of environmental conditions in several four-star hotels. The research findings can help hotel managers and local governments in improving sustainability and environmental management in the hotel industry. Specifically, the study focuses on aspects such as clean water, wastewater, ambient air, waste management, and noise pollution. The study results show that although the ambient air quality around four-star hotels meets quality standards, several parameters exceed the threshold. The concentration of BOD and COD of the effluent from filter unit are 36,8 mg/l (standard 28 mg/l) and 72,5 mg/l (standard 50 mg/l), respectively. Wastewater from hotels significantly exceeds water quality standards, while the use of filters reduces the negative impact of wastewater pollution. The research serves as a contribution to the development of future studies related to environmental quality and workplace conditions in the Indonesian hotel industry.